Application of Rolling and Areola Massage Using Jitu Oil with Murottal Al Qur'an Relaxation for Smooth Exclusive Breastfeeding - Ningsih, Dewi Andariya; Yunarsih, Nani; Sakinah, Innama; Devi Oktavia, Liana (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Lack of activation of the hormones prolactin and oxytocin can result in irregular milk production after delivery. Areola and rolling massage is a strategy to deal with erratic milk production. Jitu Oil and murottal Al-Quran can help mothers feel more comfortable and comfortable thereby encouraging more milk production. The aim of the research is to explain and examine how the effect of rolling and areola massage using precise oil and murottal Al-Qur'an relaxation on the smooth release of exclusive breastfeeding. Questionnaires and observation notes were the tools used. Instrument validity test out of 19 questions, 2 were invalid, so there were 17 questions used by researchers to measure the smoothness of breastfeeding. The results of the Wilcoxon Pretest and Posttest on the Smooth Expulsion of Exclusive Breast Milk have increased. The results of the Wilcoxon test on days 1 to 7 showed an increase in the baby's weight between the pretest and posttest which was significantly different with all respondents experiencing an increase in the baby's weight. In conclusion, rolling and areola massage using sniper oil and relaxing Al-Qur'an murottal can help expedite the smoothness of breast milk.